The effects of violent strikes on the economy of a developing country: A case of South Africa - Tenza, Mlungisi (Obiter, 2020)
The issue of violent and lengthy strikes has been a feature of South Africa’s industrial relations for a while now. There are no mechanisms in place to curb violent strikes even though their effects are visible in all corners of the Republic. Violent and lengthy strikes have devastating effects on the economy, cause injury to members of the community and non-striking workers, and more particularly poverty as employers would retrench workers if their businesses do not make profit as a result of prolonged non-production. In the mining sector where strikes are a common feature, it has been reported that employers have lost billions of rands through lengthy and violent strikes. The article acknowledges the developments brought about by amendments in the Labour Relations Act, which appears to be short of addressing the situation. The article proposes that if interest arbitration can be introduced into the Labour Relations Act, the situation may change for the better as employers and unions will be compelled to resolve their dispute(s) within a short space of time. It further submits that a strike should be allowed to proceed only if it is lawful and does not involve violence. In addition, the Labour Court should be empowered to intervene in instances where violence has developed and force the parties to arbitration.